Development of Ultra-Fast Surface Acoustic Wave-Based NO2 Sensor Incorporating a Monolayered Graphene: MoS2 Sensing Material and a Microheater for Spacecraft Applications - Nawaz, Faisal; Lee, Hyunho; Wang, Wen; Lee, Keekeun (Applied Sciences (Switzerland), 2025)
A surface acoustic wave-based NO2 sensor and its interface electronics, utilizing monolayered two-dimensional sensing materials, were developed for internal pollution monitoring in spacecraft. The sensor system consists of a two-port SAW delay line with monolayered graphene/MoS2 flakes in the cavity region between two interdigital transducers, along with the interface electronics. A microheater was integrated adjacent to the sensor to maintain a stable temperature field on the sensor surface, thereby enhancing sensitivity, response/recovery times, and selectivity. The monolayered graphene/MoS2 sensing material, with its high surface-to-volume ratio, excellent mobility, and moderate bonding force with target molecules, enables the rapid response and recovery times of less than 2.5 and 8 s, respectively—among the fastest reported in SAW gas sensor technology. The developed sensor combines the conductivity changes, the mass loading effect, and a synergistic effect that promotes carrier separation caused by a built-in potential barrier between the two monolayers, providing exceptionally high sensitivity of 578 Hz/ppm. Additionally, the sensor’s interface electronics were engineered to mitigate the effects of external factors, such as temperature and humidity, ensuring a stable and reliable performance under varying harsh conditions.
Keywords: 2d sensing material; A-stable; Graphene/MoS2 heterostructure; Graphenes; Interface electronics; Microheater; MoS 2; NO 2 sensor; Sensing material; Surface acoustic waves; 2D sensing material; graphene/MoS2 heterostructure; interface electronics; NO2 sensor; spacecraft; surface acoustic wave